PELOLOSAN GIBRAN SEBAGAI CALON WAKIL PRESIDEN (KECACATAN PENGAMBILAN KEPUTUSAN DALAM PEREVISIAN UU PEMILU) - Laily Maghfiroh; Muhammad Dewanto Adi Saputra; Regita Fakhira; Fortius Leonard (Esensi Hukum, 2024)
This paper discusses a juridical analysis of the nomination of Gibran Rakabuming Raka as the Vice Presidential candidate of the Republic of Indonesia in the 2024 General Election, which was triggered by the Constitutional Court's Decision Number 90/PUU-XXI/2023 concerning the age limit for presidential and vice-presidential candidates. This study aims to examine the validity of the decision-making process in the context of the principles of the rule of law, particularly the principles of justice, judicial independence, and constitutional ethics. The research employs a normative juridical approach and literature study of statutory regulations, Constitutional Court decisions, and opinions of constitutional law experts. The analysis reveals that the change in the age limit norm through the Constitutional Court’s decision contains ethical and legal defects, particularly related to a conflict of interest involving the Chief Justice at that time, Anwar Usman. These findings indicate that Gibran Rakabuming’s nomination is not merely a matter of formal legality but also reflects the weakened integrity of constitutional institutions that are supposed to uphold justice in a democratic system. Therefore, it is necessary to strengthen the oversight mechanisms of constitutional judicial bodies to prevent abuse of power.